Foot Squamous Cell Carcinoma: Grieve Lessons from Diabetic Foot Ulcer Misdiagnosis - Ahmedy, Fatimah; Teoh, Kean Hooi; Azizan, Nornazirah; Nik Lah, Nik Amin Sahid; Chung, Tze Yang (Gazi University, 2019)
Foot squamous cell carcinoma (SCC) is rare and preponderance towards DFU misdiagnosis is very likely given the high risk of developing DFU among diabetics. This case highlights the needs to identify atypical features observed in any given DFU to avoid misdiagnosis and late detection of malignant changes. A 63-year-old gentleman with diabetes presented with non-healing right DFU for more than two years. The ulcer was hypergranulating over medial surface of mid-foot, had minimal slough and irregular edges but no callosities. Treatments include debridement, dressing and strict offloading of right foot, but the ulcer remained unchanged. Skin biopsy confirmed the diagnosis of SCC and surgical resection was done but complicated with bone metastases at 4 months post-surgery. The patient died secondary to bilateral pulmonary embolism in less than a year since the diagnosis of SCC. Atypical features that triggered the possibility of DFU misdiagnosis are: 1) prolonged non-healing DFU despite appropriate ulcer management and addressing factors affecting wound healing, 2) foot ulcer pain with no callosities typically observed in DFU, and 3) hypergranulating ulcer in a well-controlled diabetes. Reported cases of foot SCC were primarily over the heel, an area with high contact and pressure load during walking. In this case, the absence of great toe (acquired from old trauma) had possibly altered pressure distribution of the foot leading to atypical ulcer’s location. Prolonged non-healing DFU despite appropriate ulcer management and addressing factors affecting wound healing, with atypical clinical features should raise caveat of DFU misdiagnosis. © Copyright 2019 by Gazi University Medical Faculty